Comparative Biochemistry of Four Polyester (PET) Hydrolases. (10th February 2021) - Bååth, Jenny Arnling; Borch, Kim; Jensen, Kenneth; Brask, Jesper; Westh, Peter
Abstract: The potential of bioprocessing in a circular plastic economy has strongly stimulated research into the enzymatic degradation of different synthetic polymers. Particular interest has been devoted to the commonly used polyester, poly(ethylene terephthalate) (PET), and a number of PET hydrolases have been described. However, a kinetic framework for comparisons of PET hydrolases (or other plastic‐degrading enzymes) acting on the insoluble substrate has not been established. Herein, we propose such a framework, which we have tested against kinetic measurements for four PET hydrolases. The analysis provided values of k cat and K M, as well as an apparent specificity constant in the conventional units of M −1 s −1 . These parameters, together with experimental values for the number of enzyme attack sites on the PET surface, enabled comparative analyses. A variant of the PET hydrolase from Ideonella sakaiensis was the most efficient enzyme at ambient conditions; it relied on a high k cat rather than a low K M . Moreover, both soluble and insoluble PET fragments were consistently hydrolyzed much faster than intact PET. This suggests that interactions between polymer strands slow down PET degradation, whereas the chemical steps of catalysis and the low accessibility associated with solid substrate were less important for the overall rate. Finally, the investigated enzymes showed a remarkable substrate affinity, and reached half the saturation rate on PET when the concentration of attack sites in the suspension was only about 50 nM. We propose that this is linked to nonspecific adsorption, which promotes the nearness of enzyme and attack sites. Abstract : Mass‐action kinetics for enzymatic PET hydrolysis : Four PET hydrolases have been tested within a kinetic framework for comparing enzymes hydrolysing the insoluble polymer PET. Analysis provided kinetic parameters in units of M −1  s −1, as well as values for the number of enzyme attack sites on the PET surface. This makes Michaelis–Menten kinetics possible for plastic‐degrading enzymes.